Comprehensive Physiology 2019
DOI: 10.1002/cphy.c190011
|View full text |Cite
|
Sign up to set email alerts
|

Sex, Gender, and Sex Hormones in Pulmonary Hypertension and Right Ventricular Failure

Abstract: Pulmonary hypertension (PH) encompasses a syndrome of diseases that are characterized by elevated pulmonary artery pressure and pulmonary vascular remodeling and that frequently lead to right ventricular (RV) failure and death. Several types of PH exhibit sexually dimorphic features in disease penetrance, presentation, and progression. Most sexually dimorphic features in PH have been described in pulmonary arterial hypertension (PAH), a devastating and progressive pulmonary vasculopathy with a 3-year survival … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
97
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(115 citation statements)
references
References 504 publications
(716 reference statements)
5
97
2
1
Order By: Relevance
“…What's more, there are studies have reported that gender-based differences in PAH prevalence appear to be diminished among older patients [42]. Therefore, an another important modifier of the relationship between gender and outcomes in PAH may be is age, which suggests that temporal changes in the hormonal milieu may impact disease risk and severity throughout the lifespan [43]. Just as we discussed before, race/ethnicity may also modify the relationship between sex and PAH.…”
Section: Discussionmentioning
confidence: 84%
“…What's more, there are studies have reported that gender-based differences in PAH prevalence appear to be diminished among older patients [42]. Therefore, an another important modifier of the relationship between gender and outcomes in PAH may be is age, which suggests that temporal changes in the hormonal milieu may impact disease risk and severity throughout the lifespan [43]. Just as we discussed before, race/ethnicity may also modify the relationship between sex and PAH.…”
Section: Discussionmentioning
confidence: 84%
“…on MCT-induced PH in male rats, and more research is needed to generalize our data. Thus, one should keep in mind that other results could be obtained in the case of using (1) female rats, since PAH develops predominantly in woman [ 27 ]; (2) other models of experimental PH, e.g., stimulated by hypoxia; (3) therapeutic paradigms of CBD administration; (4) other routes of its administration; (5) a higher dose or a longer period of treatment; and (6) a combination of CBD with other drugs approved for PH therapy (e.g., antagonists of endothelin receptors, bosentan or sildenafil, alone failed to modify lung weight in MCT-induced PH in rats; it was reduced only in response to a combination of both compounds [ 51 ])—a drug combination using CBD may be effective in the reduction of cardiac hypertrophy and lung edema. The anti-inflammatory effect of CBD also requires careful examination, especially in lungs.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the aim of our study was to examine the effects of chronic preventive treatment with CBD in rat experimental pulmonary hypertension (PH). Note that the terms “PAH” and “PH” are reserved for the human and experimental conditions, respectively [ 24 , 25 , 26 , 27 ]. To evaluate the efficacy of CBD in PH, right ventricular systolic pressure (RVSP), relaxant-constrictor responses and remodeling of isolated PAs, as well as parameters of hemostasis and levels of endocannabinoids and/or endocannabinoid-like compounds in rat monocrotaline (MCT)-induced PH were measured.…”
Section: Introductionmentioning
confidence: 99%
“…This may result from the fact that these treatments target pulmonary vascular dysfunction, which may result in an improvement of RV function, which may be secondary to decreased RV afterload. So, it is imperative to develop cardioprotective treatments which aim primarily to improve RV function, especially because patients often present in clinic at a later stage of the disease, when the RV dysfunction has been established [ 14 ]. Benefits of using a PTB model includes investigation of RVH and RHF independent from changes in pulmonary microvascular tone or remodeling, as well as permitting development of therapeutics that aim to improve RV function independent of changes in the afterload.…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to other models of PAH (such as Sugen and monocrotaline-induced PAH), the pulmonary trunk banding model can allow for the investigation of direct cardiac effects of an intervention on the RV, independently of the pulmonary vasculature. To date, no study has investigated sex differences in early RV gene expression in this model; our study aims to compare and investigate differential RV response to pressure overload in male vs. female rats [ 14 ].…”
Section: Introductionmentioning
confidence: 99%